Durability and degradation mechanism of GFRP bars embedded in concrete beams with cracks. (2nd January 2017) - He, X. J.; Dai, L.; Yang, W. R.
ABSTRACT: This paper reports an experimental study on the durability performance of glass fibre-reinforced polymer (GFRP) bars embedded in concrete beams with cracks. Accelerated tests were performed by immersing the beams in an alkaline solution at 60°C and in tap water at 23°C. Tensile tests were conducted to evaluate the residual tensile properties of the aged GFRP bars. Moreover, scanning electron microscopy, Fourier transform infra-red spectroscopy and differential scanning calorimetry were employed to observe and analyse potential deterioration of the fibres, matrix and fibre/matrix interface. The results showed that the tensile strength of the GFRP bars embedded in concrete beams decreased in all the different environments tested, and most of the tensile strength losses occurred during the initial stage. Actually, compared to the accelerated aging environment, the degradation of the tensile strength of GFRP bars embedded in concrete in the real-world environment is minor because the concrete, which has superior barrier properties, acts like a protective cover for the GFRP bar. Based on the test results, it can be concluded that a crack in concrete may increase the environment effect on the durability performance of the GFRP bar, but cannot change the mechanisms of mechanical degradation of the GFRP bar. In addition, the degradation rate of the GFRP bar was accelerated by sustained flexural loading. Consequently, it is important to restrain and alleviate the combined interaction of a harsh environment and sustained loading in practical engineering to enhance the durability of GFRP bars.